Polyvinyl chloride sheath material for double-core optical fiber cable and preparation method of polyvinyl chloride sheath material

By using specific formulas of polyvinyl chloride sheathing and process treatment in fiber optic cables, the problems of heat weight loss and heat shrinkage of ordinary sheathing are solved, and the service life and construction convenience are improved.

CN119241964APending Publication Date: 2025-01-03CGN TOP (SICHUAN) NEW MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411437903.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The sheath weight loss and heat shrinkage of ordinary polyvinyl chloride fiber cable jackets lead to reduced mechanical performance, short service life and difficult to tear and separate the two fiber cables, affecting the convenience of construction.

Method used

Sheathing using polyvinyl chloride resin, plasticizer, epoxy soybean oil, calcium carbonate, polymethyl methacrylate, environmentally friendly stabilizer, polyethylene wax, antioxidants, stearic acid and nano-alumina components The material formula is made by double-step screw extrusion and hot-cut granulation process, combined with drying treatment to prepare a sheath material with low heat shrinkage and high mechanical properties.

Benefits of technology

It significantly reduces the thermal weight loss and heat shrinkage of the polyvinyl chloride sheath material, improves service life, and makes the two optical fiber lines of the double-core optical fiber cable easier to tear and separate, making it easier to use in construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241964A_ABST
    Figure CN119241964A_ABST
Patent Text Reader

Abstract

The invention discloses a polyvinyl chloride sheath material for a double-core optical fiber cable and a preparation method of the polyvinyl chloride sheath material, and relates to the technical field of wire and cable materials. The invention discloses a polyvinyl chloride sheath material for a double-core optical fiber cable. Comprising the following components in parts by weight: 80 to 120 parts of polyvinyl chloride resin, 25 to 35 parts of plasticizer, 2 to 8 parts of epoxidized soybean oil, 38 to 46 parts of calcium carbonate, 0.6 to 1.4 parts of polymethyl methacrylate, 2 to 3 parts of environment-friendly stabilizer, 0.4 to 1.2 parts of polyethylene wax, 0.1 to 0.3 part of antioxidant, 0.1 to 0.3 part of stearic acid, 4 to 8 parts of nano aluminum oxide and 2 to 4 parts of PVC processing modifier. The polyvinyl chloride sheath material has low thermal aging quality loss and low thermal shrinkage, the service life is prolonged, the two optical fibers of the double-core optical fiber cable can be torn and separated more easily, and construction and use are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of wire and cable materials, and in particular to a polyvinyl chloride sheath material for a dual-core optical fiber cable and a preparation method thereof. Background Art

[0002] Dual-core fiber optic cable is composed of two parallel cables tightly bonded together (structure such as Figure 2 As shown), the sheath layers of the two optical fiber lines are both made of polyvinyl chloride material, and the sheath layers of the two optical fiber lines are adhered together when the polyvinyl chloride sheath layers are melted. For the convenience of construction and use, it is required that the two optical fiber lines of the dual-core optical fiber cable are easy to tear apart, and the thermal shrinkage of the sheath layer of the optical fiber cable is less than 5%. However, the thermal weight loss of the sheath layer of ordinary polyvinyl chloride optical fiber cables is often high after aging, and the thermal shrinkage is greater than 5%, and it is difficult to tear the two optical fiber cables apart. The thermal weight loss of the polyvinyl chloride sheath material after aging is mainly affected by two aspects. One is that the polyvinyl chloride material is easy to decompose under the conditions of light, heat, oxidation, etc.; the other is that the plasticizer is easy to migrate under heating conditions. Both of these factors will lead to an increase in the thermal weight loss of the polyvinyl chloride material, and the decomposition of the polyvinyl chloride material and the migration of the plasticizer will lead to a decrease in the mechanical properties of the polyvinyl chloride sheath material, and the sheath layer is easy to be brittle, which seriously reduces the service life of the polyvinyl chloride sheath layer. Based on this, the present application proposes a polyvinyl chloride sheath material for a dual-core optical fiber cable and a preparation method thereof. Summary of the invention

[0003] The main purpose of the present application is to provide a polyvinyl chloride sheath material for a dual-core optical fiber cable and a preparation method thereof, aiming to solve the technical problems of high thermal weight loss and thermal shrinkage of ordinary polyvinyl chloride optical fiber cable sheath materials.

[0004] To achieve the above-mentioned purpose, the present application proposes a polyvinyl chloride sheath material for a dual-core optical fiber cable, which comprises the following components, by weight: 80-120 parts of polyvinyl chloride resin, 25-35 parts of plasticizer, 2-8 parts of epoxidized soybean oil, 38-46 parts of calcium carbonate, 0.6-1.4 parts of polymethyl methacrylate, 2-3 parts of environmentally friendly stabilizer, 0.4-1.2 parts of polyethylene wax, 0.1-0.3 parts of antioxidant, 0.1-0.3 parts of stearic acid, 4-8 parts of nano-alumina and 2-4 parts of PVC processing modifier.

[0005] Optionally, the polyvinyl chloride resin is a calcium carbide process polyvinyl chloride resin with a degree of polymerization of 1000.

[0006] Optionally, the preparation step of the PVC processing modifier comprises:

[0007] The PVC processing modifier is prepared by polymerizing methyl methacrylate, butyl acrylate, butyl methacrylate and ethyl methacrylate together through an emulsion polymerization method.

[0008] Optionally, the plasticizer is dioctyl terephthalate.

[0009] Optionally, the antioxidant is antioxidant 1076.

[0010] Optionally, the environmentally friendly stabilizer is environmentally friendly stabilizer YC200.

[0011] The present application also proposes a method for preparing a polyvinyl chloride sheath material for a dual-core optical fiber cable, comprising the following steps:

[0012] The polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina are stirred and mixed, and then a plasticizer and epoxy soybean oil are added, stirred and heated, and then calcium carbonate is added, and the stirring and heating are continued to obtain a kneaded material;

[0013] The kneaded material is plasticized and extruded by a double-stage screw, and then hot-cut granulated to obtain a semi-finished product;

[0014] The semi-finished product is dried and then cooled to obtain a finished polyvinyl chloride sheath material.

[0015] Optionally, the step of mixing polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina, adding plasticizer and epoxy soybean oil, stirring and heating, adding calcium carbonate, and continuing stirring and heating to obtain a kneaded material comprises:

[0016] The polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina are stirred and mixed in a high-speed mixer for 1 min-3 min, and then the plasticizer and epoxy soybean oil are added, stirred and heated to 90°C-110°C, and then calcium carbonate is added, and the stirring is continued and the temperature is raised to 140°C-160°C, and then stirred for 1 min-2 min, and then the material is added to obtain a kneaded material.

[0017] Optionally, the step of subjecting the kneaded material to double-stage screw plasticizing and extrusion comprises:

[0018] The kneaded material is sequentially passed through a twin-screw extruder and a single-screw extruder for plasticization and extrusion, wherein, when the twin-screw extruder is performing plasticization and extrusion, the temperatures of the nine temperature control zones of the twin-screw extruder are respectively set to 135°C, 145°C, 145°C, 145°C, 135°C, 125°C, 115°C, and 105°C; when the single-screw extruder is performing plasticization and extrusion, the temperatures of the three temperature control zones of the single-screw extruder are respectively set to 105°C, 120°C, and 130°C, the temperature of the screen changing zone of the single-screw extruder is 138°C-142°C, and the head temperature of the single-screw extruder is 148°C-152°C.

[0019] Optionally, the step of drying the semi-finished product and then cooling it to obtain a finished polyvinyl chloride sheath material comprises:

[0020] The semi-finished product is placed in a ventilation oven for drying at a ventilation speed of 100 M 3 / h-120M 3 / h, the drying temperature is 80℃-90℃, the drying time is 8h-10h, stirring is carried out during the drying process, and after the drying is completed, the finished polyvinyl chloride sheath material is obtained through cooling and packaging.

[0021] The polyvinyl chloride sheath material of the present application adopts polyvinyl chloride resin, plasticizer, epoxy soybean oil, calcium carbonate, polymethyl methacrylate, environmental stabilizer, polyethylene wax, antioxidant, stearic acid, nano-alumina and PVC processing modifier as raw materials. Nano-alumina has a porous layered structure and a high specific surface area, which can play a certain binding role on the plasticizer, thereby slowing down the migration of the plasticizer. At the same time, since nano-alumina has a stable layered structure, it can give the material a higher dimensional stability, thereby reducing the thermal shrinkage of the polyvinyl chloride sheath material. The PVC processing modifier is an acrylic ester processing modifier, which has a multilayer polymer structure composed of two parts that are compatible and incompatible with the polyvinyl chloride resin. The part that is compatible with the polyvinyl chloride resin melts first, which plays a role in promoting melting, while the part that is incompatible with the polyvinyl chloride resin has a tendency to migrate out of the molten resin system, which plays an external lubricating role, so that the part that is incompatible with the polyvinyl chloride resin can migrate to the surface of the polyvinyl chloride resin melt, to a certain extent blocking the plasticizer in the polyvinyl chloride resin melt from migrating outward, thereby further reducing The quality loss of PVC sheathing material after aging is reduced. At the same time, PVC resin has good heat resistance and ductility, and plasticizer can further improve the ductility of PVC sheathing material. Polymethyl methacrylate and calcium carbonate have excellent compatibility with PVC resin and are suitable for filling PVC resin. Polyethylene wax can improve the gloss and processing performance of PVC sheathing material. Environmentally friendly stabilizer and antioxidant are used to increase the stability of the material. Antioxidant can protect PVC resin and prevent thermal oxidation degradation of PVC resin. Oxygenated soybean oil and stearic acid can promote uniform dispersion of each component, so that the final polyvinyl chloride sheath material has low thermal aging mass loss. When used for the sheath layer of a dual-core optical fiber cable, the thermal shrinkage of the sheath layer is low, thereby solving the problems of thermal weight loss and high thermal shrinkage of ordinary polyvinyl chloride sheath materials, and improving the service life of the polyvinyl chloride sheath material. In addition, through the formula design of the present application, the melt after extrusion can be cooled quickly, the adhesion between the melts is weakened, and the two optical fibers of the dual-core optical fiber cable are easier to tear apart, which is convenient for construction and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.

[0023] Figure 1 This is a schematic diagram of the process flow of the polyvinyl chloride sheath material described in the embodiment of the present application;

[0024] Figure 2Schematic diagram of the structure of a conventional dual-core optical fiber cable described in an embodiment of the present application. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0026] In view of the technical problems existing in the above-mentioned prior art, an embodiment of the present application provides a polyvinyl chloride sheath material for a dual-core optical fiber cable, which includes the following components, measured by weight: 80-120 parts of polyvinyl chloride resin, 25-35 parts of plasticizer, 2-8 parts of epoxidized soybean oil, 38-46 parts of calcium carbonate, 0.6-1.4 parts of polymethyl methacrylate, 2-3 parts of environmentally friendly stabilizer, 0.4-1.2 parts of polyethylene wax, 0.1-0.3 parts of antioxidant, 0.1-0.3 parts of stearic acid, 4-8 parts of nano-alumina and 2-4 parts of PVC processing modifier.

[0027] The polyvinyl chloride sheath material of the present application uses polyvinyl chloride resin, plasticizer, epoxy soybean oil, calcium carbonate, polymethyl methacrylate, environmental stabilizer, polyethylene wax, antioxidant, stearic acid, nano-alumina and PVC processing modifier as raw materials. Nano-alumina has a porous layered structure and a high specific surface area, which can play a certain binding role on the plasticizer, thereby slowing down the migration of the plasticizer. At the same time, since nano-alumina has a stable layered structure, it can give the material a higher dimensional stability, thereby reducing the thermal shrinkage of the polyvinyl chloride sheath material. The PVC processing modifier has a multilayer polymer structure composed of two parts that are compatible and incompatible with the polyvinyl chloride resin. The part that is compatible with the polyvinyl chloride resin melts first and plays a role in promoting melting, while the part that is incompatible with the polyvinyl chloride resin has a tendency to migrate out of the molten resin system and plays an external lubricating role, so that the part that is incompatible with the polyvinyl chloride resin can migrate to the surface of the polyvinyl chloride resin melt, to a certain extent blocking the plasticizer in the polyvinyl chloride resin melt from migrating outward, thereby further reducing the polyvinyl chloride. The quality loss of the sheath material after aging. At the same time, polyvinyl chloride resin has good heat resistance and ductility, and plasticizers can further improve the ductility of polyvinyl chloride sheath materials. Polymethyl methacrylate and calcium carbonate have excellent compatibility with polyvinyl chloride resin and are suitable for filling polyvinyl chloride resin. Polyethylene wax can improve the gloss and processing performance of polyvinyl chloride sheath materials. Environmentally friendly stabilizers and antioxidants are used to increase the stability of the material. Antioxidants can protect polyvinyl chloride resins and prevent thermal oxidation degradation of polyvinyl chloride resins. Epoxy soybean The oil and stearic acid can promote the uniform dispersion of each component, so that the finally obtained polyvinyl chloride sheath material has low thermal aging mass loss. When used for the sheath layer of a dual-core optical fiber cable, the thermal shrinkage of the sheath layer is low, thereby solving the problems of thermal weight loss and high thermal shrinkage of ordinary polyvinyl chloride sheath materials, and improving the service life of the polyvinyl chloride sheath material. In addition, through the formula design of the present application, the melt after extrusion can be cooled quickly, and the adhesion between the melts is weakened, so that the two optical fibers of the dual-core optical fiber cable are easier to tear apart, which is convenient for construction and use.

[0028] As an implementation method of the present application, the polyvinyl chloride resin is a calcium carbide method polyvinyl chloride resin with a degree of polymerization of 1000.

[0029] Specifically, the calcium carbide method refers to the direct synthesis of vinyl chloride monomer by the addition reaction of acetylene and hydrogen chloride in the presence of a mercuric chloride catalyst, and then polymerization to obtain polyvinyl chloride resin. The present application selects polyvinyl chloride resin with a degree of polymerization of 1000, which has good heat resistance and ductility, and is beneficial to improving the processing performance and mechanical properties of polyvinyl chloride sheath materials.

[0030] As an implementation method of the present application, the preparation steps of the PVC processing modifier include:

[0031] The PVC processing modifier is prepared by polymerizing methyl methacrylate, butyl acrylate, butyl methacrylate and ethyl methacrylate together through an emulsion polymerization method.

[0032] Specifically, the PVC processing modifier is an acrylic ester processing modifier with model number ACR-401. It is obtained by emulsion polymerization using methyl methacrylate, butyl acrylate, butyl methacrylate and ethyl methacrylate as monomers. It has a multilayer polymer structure consisting of two parts that are compatible and incompatible with the polyvinyl chloride resin. The part that is compatible with the polyvinyl chloride resin can promote melting, and the part that is compatible with the polyvinyl chloride resin plays an external lubricating role, so that the PVC processing modifier can block the plasticizer in the polyvinyl chloride resin melt from migrating outward, thereby reducing the thermal weight loss of the polyvinyl chloride sheath material and extending the service life of the polyvinyl chloride sheath material.

[0033] As an implementation method of the present application, the plasticizer is dioctyl terephthalate. Dioctyl terephthalate can enhance the heat resistance and durability of the polyvinyl chloride sheath material, increase the plasticizing performance of the polyvinyl chloride sheath material, facilitate the processing of the polyvinyl chloride sheath material, and extend the service life of the polyvinyl chloride sheath layer.

[0034] As an implementation method of the present application, the antioxidant is antioxidant 1076.

[0035] Specifically, the antioxidant 1076 is 3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, which has good heat resistance and water extraction resistance, and can effectively inhibit the thermal degradation and oxidative degradation of the polymer, thereby protecting the polyvinyl chloride resin and preventing the thermal oxidative degradation of the polyvinyl chloride resin, thereby improving the problem of high mass loss of the polyvinyl chloride sheath material after heating.

[0036] As an implementable embodiment of the present application, the environmentally friendly stabilizer is environmentally friendly stabilizer YC200.

[0037] The use of environmentally friendly stabilizers can effectively reduce pollution to the environment and harm to the human body. Since traditional stabilizers contain heavy metal elements such as lead and barium, these elements will be released during the production and use of polyvinyl chloride resin materials, causing serious harm to the environment and human health. Environmentally friendly stabilizer YC200 is a calcium zinc stabilizer with good stability and low toxicity. It will not cause pollution and harm to the environment and human body. It can effectively prevent polyvinyl chloride resin from aging, deterioration and cracking during processing and use. At the same time, environmentally friendly stabilizer YC200 not only improves the thermal stability of polyvinyl chloride materials, but also improves the melt flow performance of polyvinyl chloride.

[0038] The embodiment of the present application also provides a method for preparing a polyvinyl chloride sheath material for a dual-core optical fiber cable, such as Figure 1 As shown, the following steps are included:

[0039] The polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina are stirred and mixed, and then a plasticizer and epoxy soybean oil are added, stirred and heated, and then calcium carbonate is added, and the stirring and heating are continued to obtain a kneaded material;

[0040] The kneaded material is plasticized and extruded by a double-stage screw, and then hot-cut granulated to obtain a semi-finished product;

[0041] The semi-finished product is dried and then cooled to obtain a finished polyvinyl chloride sheath material.

[0042] The preparation method of the present application first mixes the materials at a high speed and then stirs them so that the materials can be fully mixed to obtain a kneaded material, and then the kneaded material is plasticized and extruded by a two-stage screw, and the plasticized material is hot-cut and granulated to obtain a semi-finished product, which can prevent the sheath layers of the two optical fiber lines from sticking together when melted, making it difficult to tear them apart, and then the semi-finished product is dried. The finished polyvinyl chloride sheath material finally prepared is convenient for construction and use, and can make the two optical fiber lines of the dual-core optical fiber cable easy to tear apart.

[0043] As an implementation method of the present application, the steps of mixing polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina, adding plasticizer and epoxy soybean oil, stirring and heating, adding calcium carbonate, and continuing stirring and heating to obtain a kneaded material include:

[0044] The polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina are stirred and mixed in a high-speed mixer for 1 min-3 min, and then the plasticizer and epoxy soybean oil are added, stirred and heated to 90°C-110°C, and then calcium carbonate is added, and the stirring is continued and the temperature is raised to 140°C-160°C, and then stirred for 1 min-2 min, and then the material is added to obtain a kneaded material.

[0045] The present application firstly adds polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina into a high-speed mixing mixer, stirs at a low speed to fully mix the materials, then adds plasticizer and epoxy soybean oil, stirs at a high speed and heats to 90°C-110°C, the plasticizing properties of the material are improved by the plasticizer, and in this process, the porous layered structure of the nano-alumina can restrain the plasticizer to avoid the migration of the plasticizer, then adds calcium carbonate, continues to stir at a high speed and heats to 140°C-160°C, so that the calcium carbonate can fully fill the material, and then reduces the stirring speed to obtain a kneaded material.

[0046] As an implementation method of the present application, the step of subjecting the kneaded material to double-stage screw plasticization extrusion includes:

[0047] The kneaded material is sequentially passed through a twin-screw extruder and a single-screw extruder for plasticization and extrusion, wherein, when the twin-screw extruder is performing plasticization and extrusion, the temperatures of the nine temperature control zones of the twin-screw extruder are respectively set to 135°C, 145°C, 145°C, 145°C, 135°C, 125°C, 115°C, and 105°C; when the single-screw extruder is performing plasticization and extrusion, the temperatures of the three temperature control zones of the single-screw extruder are respectively set to 105°C, 120°C, and 130°C, the temperature of the screen changing zone of the single-screw extruder is 138°C-142°C, and the head temperature of the single-screw extruder is 148°C-152°C.

[0048] The present application sequentially plasticizes and extrude the kneaded material through a twin-screw extruder and a single-screw extruder, and limits the temperature of the plasticizing and extruding process. After the kneaded material is sequentially heated and plasticized and extruded through the nine temperature control zones of the twin-screw extruder, it is then heated and plasticized and extruded through the three temperature control zones of the single-screw extruder, which can make the material have a better compression effect, improve the plasticity and fluidity of the material, ensure the plasticizing performance of the material in the subsequent hot cutting granulation process, and at the same time, promote the part of the PVC processing modifier that is compatible with the polyvinyl chloride resin to melt first, and the part that is incompatible with the polyvinyl chloride resin to migrate to the surface of the polyvinyl chloride resin melt, thereby blocking the plasticizer in the polyvinyl chloride resin melt from migrating outwards. After the kneaded material is plasticized and extruded by the twin-screw extruder and the single-screw extruder, the mechanical properties of the polyvinyl chloride sheath material can be improved, the embrittlement of the polyvinyl chloride sheath material can be reduced, and at the same time, the sheath layers of the two optical fibers can be prevented from sticking together when melted, making it difficult to tear them apart.

[0049] Specifically, in the hot-cutting granulation step, the kneaded material after plasticization and extrusion is hot-cut into columnar particles of 4 mm×4 mm×3 mm by adjusting the rotation speed of the pelletizer.

[0050] As an implementation method of the present application, the step of drying the semi-finished product and then cooling it to obtain the finished polyvinyl chloride sheath material includes:

[0051] The semi-finished product is placed in a ventilation oven for drying at a ventilation speed of 100 M 3 / h-120M 3 / h, the drying temperature is 80℃-90℃, the drying time is 8h-10h, stirring is carried out during the drying process, and after the drying is completed, the finished polyvinyl chloride sheath material is obtained through cooling and packaging.

[0052] The above technical solution of the present application is described in detail below in conjunction with specific embodiments.

[0053] Example 1

[0054] A polyvinyl chloride sheath material for a double-core optical fiber cable is prepared by the following steps:

[0055] 100 kg of polyvinyl chloride resin, 2.5 kg of environmental stabilizer, 0.8 kg of polyethylene wax, 0.2 kg of antioxidant, 1.0 kg of polymethyl methacrylate, 0.2 kg of stearic acid, 3 kg of PVC processing modifier and 6 kg of nano-alumina were mixed in a high-speed mixer at low speed for 2 min, 30 kg of plasticizer and 5 kg of epoxy soybean oil were added, the mixture was stirred at high speed and heated to 100° C., 43 kg of calcium carbonate was added, the mixture was stirred at high speed and heated to 150° C., and the mixture was stirred at low speed for 1.5 min, and then the mixture was discharged to obtain a kneaded material;

[0056] The polyvinyl chloride resin is a carbide-processed polyvinyl chloride resin with a polymerization degree of 1000; the PVC processing modifier is obtained by emulsion polymerization of methyl methacrylate, butyl acrylate, butyl methacrylate and ethyl methacrylate; the plasticizer is dioctyl terephthalate; the antioxidant is antioxidant 1076; the environmentally friendly stabilizer is environmentally friendly stabilizer YC200;

[0057] The kneaded material is sequentially passed through a twin-screw extruder and a single-screw extruder for plasticization and extrusion, wherein when the twin-screw extruder is plasticizing and extruding, the temperatures of the nine temperature control zones of the twin-screw extruder are respectively set to 135°C, 145°C, 145°C, 145°C, 135°C, 125°C, 115°C, and 105°C; when the single-screw extruder is plasticizing and extruding, the temperatures of the three temperature control zones of the single-screw extruder are respectively set to 105°C, 120°C, and 130°C, the temperature of the screen changing zone of the single-screw extruder is 140°C, and the temperature of the head of the single-screw extruder is 150°C, and then hot cutting and granulation are performed, and the kneaded material after plasticization and extrusion is hot cut into columnar particles of 4mm×4mm×3mm by adjusting the rotation speed of the pelletizer to obtain a semi-finished product;

[0058] The semi-finished product is placed in a ventilation oven for drying at a ventilation speed of 110 M 3 / h, drying temperature is 85℃, drying time is 9h, stirring is performed during the drying process, and after drying, the finished polyvinyl chloride sheath material is obtained through cooling and packaging. It is recorded as sample No. 1.

[0059] Example 2

[0060] A polyvinyl chloride sheath material for a double-core optical fiber cable is prepared by the following steps:

[0061] 80kg of polyvinyl chloride resin, 2kg of environmental stabilizer, 0.4kg of polyethylene wax, 0.1kg of antioxidant, 0.6kg of polymethyl methacrylate, 0.1kg of stearic acid, 2k of PVC processing modifier and 4kg of nano-alumina were mixed at low speed in a high-speed mixer for 3min, and then 25kg of plasticizer and 2kg of epoxy soybean oil were added, and the mixture was stirred at high speed and heated to 90°C, and then 38kg of calcium carbonate was added, and the mixture was stirred at high speed and heated to 140°C, and then stirred at low speed for 2min, and then the mixture was discharged to obtain a kneaded material;

[0062] The polyvinyl chloride resin is a carbide-processed polyvinyl chloride resin with a polymerization degree of 1000; the PVC processing modifier is obtained by emulsion polymerization of methyl methacrylate, butyl acrylate, butyl methacrylate and ethyl methacrylate; the plasticizer is dioctyl terephthalate; the antioxidant is antioxidant 1076; the environmentally friendly stabilizer is environmentally friendly stabilizer YC200;

[0063] The kneaded material is sequentially passed through a twin-screw extruder and a single-screw extruder for plasticization and extrusion, wherein when the twin-screw extruder is plasticizing and extruding, the temperatures of the nine temperature control zones of the twin-screw extruder are respectively set to 135° C., 145° C., 145° C., 145° C., 135° C., 125° C., 115° C., and 105° C.; when the single-screw extruder is plasticizing and extruding, the temperatures of the three temperature control zones of the single-screw extruder are respectively set to 105° C., 120° C., and 130° C., the temperature of the screen changing zone of the single-screw extruder is 138° C., and the temperature of the head of the single-screw extruder is 148° C., and then hot cutting and granulation are performed, and the kneaded material after plasticization and extrusion is hot cut into columnar particles of 4mm×4mm×3mm by adjusting the rotation speed of the pelletizer to obtain a semi-finished product;

[0064] The semi-finished product is placed in a ventilation oven for drying at a ventilation speed of 100 M 3 / h, drying temperature is 80℃, drying time is 10h, stirring is performed during the drying process, and after drying, the finished polyvinyl chloride sheath material is obtained through cooling and packaging. It is recorded as sample No. 2.

[0065] Example 3

[0066] A polyvinyl chloride sheath material for a double-core optical fiber cable is prepared by the following steps:

[0067] 120kg of polyvinyl chloride resin, 3kg of environmentally friendly stabilizer, 1.2kg of polyethylene wax, 0.3kg of antioxidant, 1.4kg of polymethyl methacrylate, 0.3kg of stearic acid, 4kg of PVC processing modifier and 8kg of nano-alumina were mixed in a high-speed mixer at low speed for 1min, 35kg of plasticizer and 8kg of epoxy soybean oil were added, the mixture was stirred at high speed and heated to 110°C, 46kg of calcium carbonate was added, the mixture was stirred at high speed and heated to 160°C, and the mixture was stirred at low speed for 1min before being discharged to obtain a kneaded material;

[0068] The polyvinyl chloride resin is a carbide-processed polyvinyl chloride resin with a polymerization degree of 1000; the PVC processing modifier is obtained by emulsion polymerization of methyl methacrylate, butyl acrylate, butyl methacrylate and ethyl methacrylate; the plasticizer is dioctyl terephthalate; the antioxidant is antioxidant 1076; the environmentally friendly stabilizer is environmentally friendly stabilizer YC200;

[0069] The kneaded material is sequentially passed through a twin-screw extruder and a single-screw extruder for plasticization and extrusion, wherein when the twin-screw extruder is plasticizing and extruding, the temperatures of the nine temperature control zones of the twin-screw extruder are respectively set to 135° C., 145° C., 145° C., 145° C., 135° C., 125° C., 115° C., and 105° C.; when the single-screw extruder is plasticizing and extruding, the temperatures of the three temperature control zones of the single-screw extruder are respectively set to 105° C., 120° C., and 130° C., the temperature of the screen changing zone of the single-screw extruder is 142° C., and the temperature of the head of the single-screw extruder is 152° C., and then hot cutting granulation is performed, and the kneaded material after plasticization and extrusion is hot cut into columnar particles of 4mm×4mm×3mm by adjusting the rotation speed of the pelletizer to obtain a semi-finished product;

[0070] The semi-finished product is placed in a ventilation oven for drying at a ventilation speed of 120 M 3 / h, drying temperature is 90℃, drying time is 8h, stirring is performed during the drying process, and after drying, the finished polyvinyl chloride sheath material is obtained through cooling and packaging. It is recorded as sample No. 3.

[0071] Example 4

[0072] A polyvinyl chloride sheath material for a double-core optical fiber cable is prepared by the following steps:

[0073] 95 kg of polyvinyl chloride resin, 2 kg of environmentally friendly stabilizer, 1.0 kg of polyethylene wax, 0.1 kg of antioxidant, 0.8 kg of polymethyl methacrylate, 0.3 kg of stearic acid, 2 kg of PVC processing modifier and 5 kg of nano-alumina were mixed in a high-speed mixer at low speed for 1 min, and then 28 kg of plasticizer and 4 kg of epoxy soybean oil were added, and the mixture was stirred at high speed and heated to 105° C., and then 44 kg of calcium carbonate was added, and the mixture was stirred at high speed and heated to 145° C., and then stirred at low speed for 1 min, and then the mixture was discharged to obtain a kneaded material;

[0074] The polyvinyl chloride resin is a carbide-processed polyvinyl chloride resin with a polymerization degree of 1000; the PVC processing modifier is obtained by emulsion polymerization of methyl methacrylate, butyl acrylate, butyl methacrylate and ethyl methacrylate; the plasticizer is dioctyl terephthalate; the antioxidant is antioxidant 1076; the environmentally friendly stabilizer is environmentally friendly stabilizer YC200;

[0075] The kneaded material is sequentially passed through a twin-screw extruder and a single-screw extruder for plasticization and extrusion, wherein when the twin-screw extruder is plasticizing and extruding, the temperatures of the nine temperature control zones of the twin-screw extruder are respectively set to 135°C, 145°C, 145°C, 145°C, 135°C, 125°C, 115°C, and 105°C; when the single-screw extruder is plasticizing and extruding, the temperatures of the three temperature control zones of the single-screw extruder are respectively set to 105°C, 120°C, and 130°C, the temperature of the screen changing zone of the single-screw extruder is 140°C, and the temperature of the head of the single-screw extruder is 150°C, and then hot cutting and granulation are performed, and the kneaded material after plasticization and extrusion is hot cut into columnar particles of 4mm×4mm×3mm by adjusting the rotation speed of the pelletizer to obtain a semi-finished product;

[0076] The semi-finished product is placed in a ventilation oven for drying at a ventilation speed of 115 M 3 / h, drying temperature is 82℃, drying time is 8h, stirring is performed during the drying process, and after drying, the finished polyvinyl chloride sheath material is obtained through cooling and packaging. It is recorded as sample No. 4.

[0077] Comparative Example 1

[0078] Compared with Example 1, nano-alumina was not added, and the remaining steps were the same. This was recorded as Sample No. 5.

[0079] Comparative Example 2

[0080] Compared with Example 1, no PVC processing modifier was added, and the remaining steps were the same. This was recorded as Sample No. 6.

[0081] Experimental example

[0082] The sheath layers made of sample No. 1, sample No. 2, sample No. 3, sample No. 4, sample No. 5 and sample No. 6 were respectively made into dumbbell specimens according to GB / T12706.2-2020 standard, and were marked as sample No. 1, sample No. 2, sample No. 3, sample No. 4, sample No. 5 and sample No. 6, respectively. Then, the mass loss and thermal shrinkage of sample No. 1, sample No. 2, sample No. 3, sample No. 4, sample No. 5 and sample No. 6 were measured after aging treatment at 100°C in an oven for 240 hours. The test results are shown in Table 1.

[0083] Table 1

[0084] Group <![CDATA[Mass loss (g / m 2 )]]> Thermal shrinkage (%) Sample No. 1 2.5 2.0 Sample No. 2 4.5 3.8 Sample No. 3 3.3 2.6 Sample No. 4 3.6 2.2 Sample No. 5 8.0 5.2 Sample No. 6 12.5 6.1

[0085] As can be seen from Table 1, after aging at 100°C for 240h, the mass loss of the sheath layer prepared in the embodiment of the present application is 2.5g / m 2 -4.5g / m 2 The thermal shrinkage is between 2.0% and 3.8%. Since the sheath layer prepared in Comparative Example 1 does not contain nano-alumina, the plasticizer is easy to migrate under heating conditions, resulting in a significant increase in the mass loss and thermal shrinkage of the sheath layer after heating. Since the sheath layer in Comparative Example 2 does not contain PVC processing modifier, the polyvinyl chloride resin is easy to decompose under heating conditions, and the plasticizer migrates, which leads to a significant increase in the mass loss and thermal shrinkage of the sheath layer after heating.

[0086] The above description is only an optional embodiment of the present application, and does not limit the patent scope of the present application. All equivalent structural transformations made using the contents of the present application specification under the inventive concept of the present application, or direct / indirect application in other related technical fields are included in the patent protection scope of the present application.

Claims

1. A polyvinyl chloride sheath material for a dual-core optical fiber cable, characterized in that: The composition comprises the following components in parts by weight: 80-120 parts of polyvinyl chloride resin, 25-35 parts of plasticizer, 2-8 parts of epoxy soybean oil, 38-46 parts of calcium carbonate, 0.6-1.4 parts of polymethyl methacrylate, 2-3 parts of environmentally friendly stabilizer, 0.4-1.2 parts of polyethylene wax, 0.1-0.3 parts of antioxidant, 0.1-0.3 parts of stearic acid, 4-8 parts of nano-alumina and 2-4 parts of PVC processing modifier.

2. The polyvinyl chloride sheath material for dual-core optical fiber cable according to claim 1, characterized in that: The polyvinyl chloride resin is a calcium carbide method polyvinyl chloride resin with a polymerization degree of 1000.

3. The polyvinyl chloride sheath material for dual-core optical fiber cable according to claim 1, characterized in that: The preparation steps of the PVC processing modifier include: The PVC processing modifier is prepared by polymerizing methyl methacrylate, butyl acrylate, butyl methacrylate and ethyl methacrylate together through an emulsion polymerization method.

4. The polyvinyl chloride sheath material for a dual-core optical fiber cable according to claim 1, characterized in that: The plasticizer is dioctyl terephthalate.

5. The polyvinyl chloride sheath material for double-core optical fiber cable according to claim 1, characterized in that: The antioxidant is antioxidant 1076.

6. The polyvinyl chloride sheath material for dual-core optical fiber cable according to claim 1, characterized in that: The environmentally friendly stabilizer is environmentally friendly stabilizer YC200.

7. A method for preparing a polyvinyl chloride sheath material for a dual-core optical fiber cable according to any one of claims 1 to 6, characterized in that: The following steps are involved: The polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina are stirred and mixed, and then a plasticizer and epoxy soybean oil are added, stirred and heated, and then calcium carbonate is added, and the stirring and heating are continued to obtain a kneaded material; The kneaded material is plasticized and extruded by a double-stage screw, and then hot-cut granulated to obtain a semi-finished product; The semi-finished product is dried and then cooled to obtain a finished polyvinyl chloride sheath material.

8. The method for preparing a polyvinyl chloride sheath material for a dual-core optical fiber cable according to claim 7, characterized in that: The steps of mixing polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina, adding plasticizer and epoxy soybean oil, stirring and heating, adding calcium carbonate, and continuing stirring and heating to obtain a kneaded material include: The polyvinyl chloride resin, environmental stabilizer, polyethylene wax, antioxidant, polymethyl methacrylate, stearic acid, PVC processing modifier and nano-alumina are stirred and mixed in a high-speed mixer for 1 min-3 min, and then the plasticizer and epoxy soybean oil are added, stirred and heated to 90°C-110°C, and then calcium carbonate is added, and the stirring is continued and the temperature is raised to 140°C-160°C, and then stirred for 1 min-2 min, and then the material is added to obtain a kneaded material.

9. The method for preparing a polyvinyl chloride sheath material for a dual-core optical fiber cable according to claim 7, characterized in that: The step of subjecting the kneaded material to double-stage screw plasticizing and extrusion comprises: The kneaded material is sequentially passed through a twin-screw extruder and a single-screw extruder for plasticization and extrusion, wherein, when the twin-screw extruder is performing plasticization and extrusion, the temperatures of the nine temperature control zones of the twin-screw extruder are respectively set to 135°C, 145°C, 145°C, 145°C, 135°C, 125°C, 115°C, and 105°C; when the single-screw extruder is performing plasticization and extrusion, the temperatures of the three temperature control zones of the single-screw extruder are respectively set to 105°C, 120°C, and 130°C, the temperature of the screen changing zone of the single-screw extruder is 138°C-142°C, and the head temperature of the single-screw extruder is 148°C-152°C.

10. The method for preparing a polyvinyl chloride sheath material for a dual-core optical fiber cable according to claim 7, characterized in that: The step of drying the semi-finished product and then cooling it to obtain the finished polyvinyl chloride sheath material comprises: The semi-finished product is placed in a ventilation oven for drying at a ventilation speed of 100 M 3 / h-120M 3 / h, the drying temperature is 80℃-90℃, the drying time is 8h-10h, stirring is carried out during the drying process, and after the drying is completed, the finished polyvinyl chloride sheath material is obtained through cooling and packaging.

Citation Information

Cited By

  • Epoxy fatty acid methyl ester wire and cable material and preparation method thereof

    CN119899473A